Effect of resistance training on the biomechanics and accuracy of serve receiving skills in volleyball - Muna Taha Idrees; Alaa Muhsun Yasir; Jasim Mohammed Rashied (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.